2001
DOI: 10.1021/ie000502l
|View full text |Cite
|
Sign up to set email alerts
|

Depolymerization of Styrene−Butadiene Copolymer in Near-Critical and Supercritical Water

Abstract: Many conventional solvents do not sufficiently dissolve cross-linked polymers such as styrenebutadiene rubber (SBR) to allow efficient depolymerization. Supercritical and near-critical water provides an alternative benign solvent for this application. Supercritical water oxidation and thermal degradation under supercritical water conditions provide a means to break down rubbery materials into organic compounds that can then be recovered as a chemical feedstock. In this study, depolymerization reactions of styr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Single synthetic polymers subcritical HTL has been reported for specific materials in several publications, including reports on HTL of: high-impact polystyrene, poly-acrylonitrile-butadiene-styrene (ABS), polycarbonate and polyamide 6 (Iwaya et al, 2006;Zhao et al, 2018a); epoxy printed circuit boards (Yildirir et al, 2015); polyethylene naphthalate and terephthalate (Arai et al, 2010;Zenda and Funazukuri, 2008); polystyrene-butadiene (Park et al, 2001); polyurethane (Dai et al, 2002). These studies show that monomers, other valuable chemical compounds or an oil product may be recovered using HTL.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Single synthetic polymers subcritical HTL has been reported for specific materials in several publications, including reports on HTL of: high-impact polystyrene, poly-acrylonitrile-butadiene-styrene (ABS), polycarbonate and polyamide 6 (Iwaya et al, 2006;Zhao et al, 2018a); epoxy printed circuit boards (Yildirir et al, 2015); polyethylene naphthalate and terephthalate (Arai et al, 2010;Zenda and Funazukuri, 2008); polystyrene-butadiene (Park et al, 2001); polyurethane (Dai et al, 2002). These studies show that monomers, other valuable chemical compounds or an oil product may be recovered using HTL.…”
Section: Introductionmentioning
confidence: 89%
“…A similar polymer to PS, a co-polymer of styrene with butadiene, has been reported to decompose in the presence of water at 350 ºC with depolymerization as high as 61% for a reaction time of 60 min. (Park et al, 2001) Near supercritical HTL (370 ºC) was also reported to decompose PS into valuable chemicals in short residence times (Kwak et al, 2005), however, supercritical PS HTL (Kwak et al, 2005;Park et al, 2001) was recently found to have the most efficient condition at 490 ºC with carbon liquefaction efficiency as high as 80%. (Bai et al, 2019) In the present study, the aromatic-containing polymer PS has shown to be stable under subcritical conditions.…”
Section: Hdpe Ldpe Pp and Psmentioning
confidence: 99%
“…Park et al employed partial oxidation in the semi-batch reactor and obtained various product of destruction including benzene, toluene, ethylbenzene, styrene, phenol, acetophenone, benzaldehyde, and benzoic acid [58]. Partial oxidation is addition of small amount of oxygen, which is not sufficient for complete oxidation of the feedstock.…”
Section: Waste Plastics and Waste Rubbermentioning
confidence: 99%
“…Results are in good agreement with experimental data only at low conversions. Park et al15 studied the depolymerization of styrene–butadiene copolymer in near‐critical and supercritical water in a batch reactor using a detailed statistical analysis. Kao et al16 determined the kinetics of hydrolytic depolymerization of melting PET in a batch reactor considering an autocatalytic mechanism.…”
Section: Introductionmentioning
confidence: 99%